Bureaucrats in Business : The Economics and Politics of Government Ownership - [Tidak Terdaftar] (Oxford University Press, 1995)
This note presents the key findings from "Bureaucrats in Business: The Economics and Politics of Government Ownership" (World Bank 1995), on the reform of state enterprises. It also assesses why so few countries are reforming. It concludes with suggestions on how the Bank can better assist countries undertaking reforms -- a) analyzing the readiness to reform systematically; b) tracking state enterprises over time; and c) measuring the success of reform efforts by assessing performance.